Impact of a colon management program on the quality of life of patients with constipation and fecal loss - Maria Giovana O. Farias; Joaquim M. Bustorff-Silva (Elsevier, 2023)
Objective: To evaluate the impact of colon management on the quality of life of patients with constipation and fecal loss. Methodology: We selected 10 patients with incontinence from 4 to 18 years of age who participated in the colon management program for the treatment of fecal incontinence. They underwent the application of a Questionnaire to assess the quality of life of life related to fecal continence in children and adolescents (QQVCFCA) before and after the application of the program. The same questionnaire was applied to a control group, made up of 10 children without fecal incontinence, in order to carry out a comparative analysis between the groups. Results: There was a statistically significant improvement in quality of life in all participants in the cervical management program (p<0.05; CI > 95%) The post-program quality of life index reached levels similar to those observed among children in the control group. Conclusion: In this way, we conclude that the well-structured colon management program, with individualized therapeutic proposals and based on clinical history, on the pathophysiology of constipation/fecal leakage and on the anatomical changes observed in the contrast enema, performed when the child is admitted to the program, allows us to classify patients well and establish adequate therapy, minimizing the costs and associated risks, ensuring that they can fulfill their social functions, physical sports and leisure activities without compromising their quality of life.